Marginalités et fantaisies linguistiques chez Boris Vian. - Khebbab, khaoula (Journal of Human Sciences, 2018)
In this analysis we are interested in certain stylistic and rhetorical aspects in three Birus Vian novels texts. We wonder about the various processes used by the author for his verbal-linguistic creations. Our goal is to identify the marginal feature of Vian's work and to understand its mechanism.